Polychlorinated biphenyls disrupt hepatic epidermal growth factor receptor signaling. (2nd September 2017) - Hardesty, Josiah E.; Wahlang, Banrida; Falkner, K. Cameron; Clair, Heather B.; Clark, Barbara J.; Ceresa, Brian P.; Prough, Russell A.; Cave, Matthew C.
Abstract: 1. Polychlorinated biphenyls (PCBs) are persistent environmental pollutants that disrupt hepatic xenobiotic and intermediary metabolism, leading to metabolic syndrome and nonalcoholic steatohepatitis (NASH). 2. Since phenobarbital indirectly activates Constitutive Androstane Receptor (CAR) by antagonizing growth factor binding to the epidermal growth factor receptor (EGFR), we hypothesized that PCBs may also diminish EGFR signaling. 3. The effects of the PCB mixture Aroclor 1260 on the protein phosphorylation cascade triggered by EGFR activation were determined in murine ( in vitro and in vivo ) and human models ( in vitro ). EGFR tyrosine residue phosphorylation was decreased by PCBs in all models tested. 4. The IC50 values for Aroclor 1260 concentrations that decreased Y1173 phosphorylation of EGFR were similar in murine AML-12 and human HepG2 cells (∼2–4 μg/mL). Both dioxin and non-dioxin-like PCB congeners decreased EGFR phosphorylation in cell culture. 5. PCB treatment reduced phosphorylation of downstream EGFR effectors including Akt and mTOR, as well as other phosphoprotein targets including STAT3 and c-RAF in vivo . 6. PCBs diminish EGFR signaling in human and murine hepatocyte models and may dysregulate critical phosphoprotein regulators of energy metabolism and nutrition, providing a new mechanism of action in environmental diseases.